The Influence of Offline BPR Deposit Events by Komunal on Customer Funding Decision Making - Mutiara Puspa Putri Iswatie; Wiliam Santoso (JURNAL ECONOMINA, 2026)
his study aims to analyze the influence of offline events on trust, customer intention , and customer decision in placing funds in DepositoBPR by Komunal, both directly and through mediating variables of trust and customer intention . This study uses a quantitative approach with a survey method on 210 respondents, prospective customers and customers of DepositoBPR by Komunal. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method through SmartPLS software. The results of the study indicate that offline events have a positive and significant effect on trust, customer intention , and customer decision . In addition, trust has a significant effect on customer intention and customer decision , while customer intention also has a significant effect on customer decision . This study also found that trust and customer intention are able to mediate the influence of offline events on customer decisions in placing funds in DepositoBPR by Komunal. The research findings confirm that marketing strategies through offline events are still effective in building trust, increasing intention, and encouraging customer funding decisions in digital financial services.